PENGARUH E-SATISFACTION DAN E-TRUST TERHADAP E-LOYALTY PENGGUNAAN APLIKASI DANA PADA MAHASISWA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI MEDAN - Hutasoit, Katrin Anastasya; Harahap, Irwan Musriza (Politeknik Negeri Ambon, 2023)
The purpose of this research aims to determine of the truth of how e-satisfaction and e-trust affect e-loyalty in the use of Dana applications for students of the Department of Trade Administration, Medan State Polytechnic. Quantitative research methods are used as this research method. The sampling method was carried out using a purposive sampling technique with 64 respondents and data collection was carried out by distributing questionnaires. This study shows that e-satisfaction and e-trust partially have a positive and significant effect on e-loyalty in the use of Dana applications for students Department of Trade Administration in Medan State Polytechnic, and simultaneously the e-Satisfaction variable and E-trust variable together has a positive and significant effect on the E-loyalty variable in the use of Dana applications for students of the Department of Trade Administration, Medan State Polytechnic. Â